Long‐term prognosis of focal segmental glomerulosclerosis treated with therapeutic low‐density lipoprotein‐apheresis in patients with severe kidney dysfunction and proteinuria. Issue 1 (27th March 2023) - Kitajima, Shinji; Osima, Megumi; Ogura, Hisayuki; Nakagawa, Shiori; Yamamura, Yuta; Miyake, Taito; Miyagawa, Taro; Toyama, Tadashi; Hara, Akinori; Sakai, Norihiko; Shimizu, Miho; Wada, Takashi; et al.
Abstract: Background: The prognosis of focal segmental glomerulosclerosis patients with nephrotic syndrome is estimated to be 10%–20% in 5 years and 30%–50% in 10 years, leading to end‐stage kidney disease. The response rate with steroid therapy is 40%–60%. Therapeutic low‐density lipoprotein‐apheresis (LDL‐A) may be effective in patients with steroid resistance. Information regarding the long‐term prognosis of patients with focal segmental glomerulosclerosis receiving this therapy is scarce. Methods: We investigated the effectiveness of treatment in 50 patients with primary focal segmental glomerulosclerosis diagnosed between 1961 and 2017 at Kanazawa University Hospital and related facilities. The patients were observed at least 12 months after biopsy or until end‐stage kidney disease occurrence or death. Results: LDL‐A was performed in four patients who presented with steroid‐resistant nephrotic syndrome (two patients had concurrent acute renal failure for which hemodialysis was performed). In comparison with 17 patients who did not receive LDL‐A after 1989, the LDL‐A group had higher urinary protein excretion (13.7 vs. 5.2 g/day, P = 0.053) and serum creatinine (4.11 vs. 1.65 mg/dL) levels at onset, and a numerically higher remission rate (75.0% vs. 58.7%) compared with the nonlipoprotein‐apheresis group. Conclusion: Therapeutic LDL‐A can be performed for critical cases and may improve the remission rate. Abstract : The prognosis of focal segmental glomerulosclerosis (FSGS) patients with nephrotic syndrome is poor. We investigated the effectiveness of treatment in 50 patients with primary FSGS. Low‐density lipoprotein‐apheresis (LDL‐A) was performed in 4 patients who presented with steroid‐resistant nephrotic syndrome. In comparison with 17 patients who did not receive LDL‐A after 1989, the LDL‐A group had higher urinary protein excretion (13.7 vs. 5.2 g/day, P = 0.053) and serum creatinine (4.11 vs. 1.65 mg/dL) levels at onset. Nevertheless, the LDL‐A group showed a numerically higher remission rate (75% vs. 59%) compared with the nonlipoprotein‐apheresis group. Key points: The prognosis of focal segmental glomerulosclerosis (FSGS) patients with nephrotic syndrome is poor. We investigated the effectiveness of treatment in 50 patients with primary FSGS. Low‐density lipoprotein‐apheresis (LDL‐A) was performed in four patients who presented with steroid‐resistant nephrotic syndrome. LDL‐A therapy tended to be chosen for more critical cases. Although it may be effective at improving the remission rate, we believe that studies on more patients are required to elucidate the effect on long‐term prognosis.